Membangun Masyarakat Bijak Bermedia Sosial di Era Digital pada SDN Pejambon, Warungasem, Batang - Anindiya Tabina Priyadi; Azzahra Citra Larrasati; Ivan Dwi Saputra; Siti Nur Amirul Lutfi; Shalsabila Melati; Farihul Izza Zam Zami; M.Ikhwan Ramadhan; Muhammad Khoirur Rofiq (Lembaga Pengembangan Kinerja Dosen, 2024)
Poorly managed social media can lead to the dissemination of inaccurate information, as well as radicalization and social conflict. Therefore, an appropriate intervention is needed to build a society that is wise in using social media, especially among students of SDN Pejambon, Warungasem, Batang. The purpose of this program is to improve media literacy and develop religious moderation skills in the use of social media among students. The method used is Participatory Action Research (PAR), which involves the community actively in every stage of the activity. Based on the results of problem formulation, a Community Service (PKM) strategy was developed to overcome these challenges. The program succeeded in increasing media literacy and awareness of religious moderation among students. The implication is that this program can be a model for other schools in building a social media-wise society in the digital era.